Physical Simulations of AlSb/InAs High Electron Mobility Transistors - Johansson, Josefin (My University, 2007)
This diploma work describes the design of a simulation model for a metamorphic AlSb/InAs High Electron Mobility Transistor (HEMT) with a very narrow InAs quantum well incorporating the delta-doping. The physical models that are incorporated are thoroughly described, as well as the material parameters necessary for the implementation of these models. A model for the impact ionization at high fields in the channel was calibrated to measurement data. DC and AC simulations were performed and compared to measurement data from devices fabricated in the Nanofabrication Laboratory at Chalmers University of Technology. The simulated results matched the measured ones reasonably well for drain voltages up to 0.2V and displayed all the expected trends. The mismatch at higher drain biases was probably due to the imperfection of the high field velocity saturation model and should be investigated more thoroughly. Finally, the simulation model was used when studying the effects of gate length variations on the transconductance and cut-off frequency.
Keywords: Elektroteknik och elektronik; Electrical Engineering, Electronic Engineering, Information Engineering